Quality response to real exchange rate shocks: A panel SVAR analysis on China's agricultural exports - Rui Mao; Mengying Xing; Xiaohua Yu (Agricultural Economics, 2021)
This article applies a panel structural VAR model using complete data of China's monthly agricultural exports to uncover both the dynamics and interproduct and intermarket differences in the responses of product quality to real exchange rate (RER) shocks. It finds that RER appreciation promotes the quality of China's agricultural exports on average compared to discouraging exports, but the effect is fully shown in the short run. The average response peaks in the month immediately after the shock and the average cumulative response converges to a constant level in three months. The quality response to RER shocks substantially differs across both products and markets. More sensitive responses of quality upgrading are found among exports that are less competitive, relatively primary, more reliant on ordinary trade, and exported with nearby and less developed partners. Therefore, greater supports on R&D activities and the adoption of advanced technologies might be needed among other exports.
Keywords: 330; agricultural export quality; panel SVAR; real exchange rate